2016
DOI: 10.3389/fneur.2016.00200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1 as a Potential Therapeutic Target for Seizure Suppression: Evidences from Zebrafish Pentylenetetrazole-Seizure Model

Abstract: Cyclooxygenases (COX)-1 and -2 are isoenzymes that catalyze the conversion of arachidonic acid into prostaglandins (PGs). COX-2 and PGs are rapidly increased following seizures and are known to play important roles in the neuroinflammatory process. COX-2 isoform has been predominantly explored as the most suitable target for pharmacological intervention in epilepsy studies, while COX-1 remains poorly investigated. In the present study, we evaluated the effects of selective COX-1 inhibitor or selective COX-2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Prior to pretreatment, a toxicology evaluation may be performed to determine the maximum-tolerated concentrations (MTCs) of the drugs utilized, to avoid toxicity. This can be performed by using test compounds and observing the effects of AEDs on affected zebrafish for a period of 24 h (Barbalho et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to pretreatment, a toxicology evaluation may be performed to determine the maximum-tolerated concentrations (MTCs) of the drugs utilized, to avoid toxicity. This can be performed by using test compounds and observing the effects of AEDs on affected zebrafish for a period of 24 h (Barbalho et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence is inconclusive on the effectivity of COX-2 therapy, and many have reported that the effects of COX-2 therapy may be highly dependent on the type of inhibitor used and the timing at which the medication is administered in relation to seizure onset. Such conflicting results are drawing attention to other targets within PG synthesis and mechanistic pathways [ 43 ]. COX-2 is upregulated by platelet-activating factor (PAF) and NMDA activation [ 7 , 44 ].…”
Section: Inflammation In the Central Nervous Systemmentioning
confidence: 99%
“…The same problem happened in the zebrafish model for epilepsy. Since the establishment of the PTZ-induced seizure model for epilepsy in zebrafish (Baraban et al, 2005), there have been rich applications (Afrikanova et al, 2013; Banote et al, 2013; Barbalho et al, 2016; Berghmans et al, 2007; Gupta et al, 2014; Hunyadi et al, 2017; Lin et al, 2018; Liu and Baraban, 2019; Mei et al, 2013; Mussulini et al, 2013; Pineda et al, 2011; Siebel et al, 2013; Tiedeken and Ramsdell, 2007; Turrini et al, 2017; Yang et al, 2017). However, the seizures induced by PTZ only cause transient acute seizures, which have poor face validity as the defining feature of epilepsy is spontaneous recurrent seizures (Johan Arief et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Once Stage III is evoked in zebrafish, it cannot be reversed by any method except the administration of AEDs (Baraban et al, 2005). Since this first demonstration of the zebrafish larval model, seizure-like responses have been described by behavioral changes in locomotor activity (Baraban et al, 2005; Barbalho et al, 2016; Berghmans et al, 2007), EEG (Pineda et al, 2011), c-fos expression (Baraban et al, 2005; Barbalho et al, 2016), optical imaging (Turrini et al, 2017), calcium imaging (Liu and Baraban, 2019), and the phosphorylation of ERK1/2 kinases (Randlett et al, 2015). The same PTZ treatment had been proven to be applicable to the adult zebrafish, and the behavioral response profile was characterized by stages that were comparable to those described for the rodent models (Afrikanova et al, 2013; Gupta et al, 2014; Mussulini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%